Torres Strait Islanders : custom and colonialism - Beckett, Jeremy (Cambridge ; Sydney : Cambridge University Press, 1987)
Cultural history of Torres Strait Islands based on archival sources and the oral record, focussing on contrasts between Badu and Murray Islands; emergence of colonial order from mid l800s; introduction of Government, mission, industry; outbreak of pacific war during WWII, collapse of pearling industry, beginning of emmigration to mainland in l960s; Islanders understanding of their history, present situation; case studies of Badu and Murray Islands, first 100 years of colonisation; recent history, emergence of welfare economy, political system, mainland TSI community; role of Island custom in mediating their relationship with Australian society in part through imposing Islander social structures on changes brought from Australian culture.
Machine derived contents note: List of plates and maps -- Preface -- List of abbreviations -- 1. A 'tombstone opening' and the problem of island custom -- 2. Pearlers, pastors and protectors -- 3. Disastrous contact: 'army time' and after -- 4. Reflections in a colonial mirror -- 5. The Murray Islanders -- 6. The Baduans -- 7. Welfare colonialism -- 8. The society of Islanders -- Bibliography -- Index.
Includes index.
Bibliography: p. 236-246.
Copy 2 - donation from Tom Austen Brown collection
Keywords: Torres Strait Islanders -- Social life and customs; Torres Strait Islands (Qld.) -- History; Torres Strait Islands (Qld.) -- Social life and customs; Torres Strait Islands (Qld.) -- Politics and government; Torres Strait Islands (Qld.) -- Colonial influence; Torres Strait Islanders - Social life and customs; Torres Strait Islands - History; Torres Strait Islands - Social life and customs